Does social vulnerability define the risk of leprosy in an endemic region? A time trend analysis in leprosy‐endemic area. (25th July 2019) - Verma, P.; Kumari, P.
Abstract : Linked article: C.D.F. de Souza et al. J Eur Acad Dermatol Venereol 2019; 33 :1581–1590. https://doi.org/10.1111/jdv.15596